Unknown Documents on the History of the Astrakhan Uprising of 1705–1706 in the Collection of Reports to Boyar T.N. Streshnev from the Foundations of the Russian National Library - Alexey Alekseev (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2023)
Introduction. The main corpus of documents on the history of the Astrakhan uprising of 1705– 1706 has been brought into scientific circulation and well studied. However, one of the most important documents – Peter I’s “Letter of Pardon” to the rebellious Astrakhans – was considered lost. Methods and materials. In the collections of the Russian National Library, we managed to find a collection of documents, which are copies of letters and relays addressed to the boyar T.N. Streshnev. It contains copies of two dozen documents for the period from 1702 to 1710. The owner of the collection of copies was a well-known representative of the bureaucracy of the first third of the 18th century, Ivan Topilsky. The manuscript should be dated to the 1720s. Analysis. The collection contains a set of four documents, which are important sources for the study of the Astrakhan uprising. Three letters are addressed to the boyar T.N. Streshnev. Only a letter from the boyar Prince Pyotr Khovansky, commander of the vanguard of B.P. Sheremetev’s troops, which reports on the mood in rebellious Astrakhan, has been introduced into scientific circulation. The letter of Field Marshal B.P. Sheremetev describes the course of hostilities during the capture of Astrakhan by government troops. The text of this letter is close to the text of the previously published letter of B.P. Sheremetev to F.A. Golovin. The letter of the Astrakhan metropolitan Samson is devoted to the description of the final stage of the pacification of the rebels. Most of the text of this document coincides with the letter of the metropolitan to Peter I, which was introduced into the scientific turnover. The fourth document is a list from the hitherto unknown “Letter of Pardon” of Peter the Great to the rebels. Familiarity with the text of the letter confirms the opinion of researchers that the letter was composed in soft tones. Peter I, having learned about the readiness of the rebels to bring their guilt to light, willingly grants them all full forgiveness with the obligation to put the rebellion in “eternal oblivion”, and never “reproach” any of the participants. Results. The text of two unpublished letters of B.P. Sheremetev and Metropolitan Samson to T.N. Streshnev, as well as the previously unknown text of Peter I’s “pardonable” letter, are introduced into scientific circulation for the first time on the basis of a list from the holdings of the Manuscripts Department of the Russian National Library.